2022
DOI: 10.1007/s11468-021-01565-9
|View full text |Cite
|
Sign up to set email alerts
|

Tuning and Sensitivity Improvement of Bi-Metallic Structure-Based Surface Plasmon Resonance Biosensor with 2-D $$\upvarepsilon$$-Tin Selenide Nanosheets

Abstract: This manuscript aims to analyze the effect of tin selenide (SnSe) on the sensing application of SPR biosensors. Tin selenide is the 2-dimensional transition metal dichalcogenide material. The proposed multilayer structure has a BK7 prism, a bimetallic layer of Au, tin selenide, and a graphene layer. Tin selenide is used to improve the performance parameters of the biosensor. The nanosheet is placed in between two layers of gold (Au) in the Kretschmann configuration. The proposed configuration has a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…These were highly sensitive and enable real-time analysis of polluted analytes in the biosensing field to detect, analyze, and describe the biomolecule, chemical, environment and food. [53] A biosensor is an analytical system that can identify a particular biological analyte and convert the presented data into analytical information such as electrical, optical, and thermal signals, through a straight forward, inexpensive and swift process. Due to their inherent enzymatic capabilities nano enzyme biosensors, including transition metal chalcogenides have seen tremendous applications in the biomedical field, particularly diagnostics, since the advent of nanotechnology.…”
Section: Biosensing Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…These were highly sensitive and enable real-time analysis of polluted analytes in the biosensing field to detect, analyze, and describe the biomolecule, chemical, environment and food. [53] A biosensor is an analytical system that can identify a particular biological analyte and convert the presented data into analytical information such as electrical, optical, and thermal signals, through a straight forward, inexpensive and swift process. Due to their inherent enzymatic capabilities nano enzyme biosensors, including transition metal chalcogenides have seen tremendous applications in the biomedical field, particularly diagnostics, since the advent of nanotechnology.…”
Section: Biosensing Applicationsmentioning
confidence: 99%
“…The biosensor has recently been used to identify the targeted viruses (CORONA), cancer cells, DNA hybridization, antibody characterization and protein conformation. These were highly sensitive and enable real‐time analysis of polluted analytes in the biosensing field to detect, analyze, and describe the biomolecule, chemical, environment and food [53] . A biosensor is an analytical system that can identify a particular biological analyte and convert the presented data into analytical information such as electrical, optical, and thermal signals, through a straight forward, inexpensive and swift process.…”
Section: Specifications Of Metal Chalcogenidesmentioning
confidence: 99%
“…Gold is a highly conductive material, especially in the terahertz frequency range. It allows for efficient transmission of electromagnetic waves and minimizes energy losses [26,27]. Gold is biocompatible, making it suitable for applications involving biological samples or environments.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their energy-efficient, light weight and great conducting properties, two-dimensional materials have been used widely in SPR sensors [10]. Previous studies have claimed that using two-dimensional nanomaterials like Perovskite materials and transition metal dichalcogenides (TMDEs) [11], graphene [12][13][14][15], Franckeite nanosheets [16], Black phosphorus [17] and Tin selenide [18] has dramatically improved the SPR sensor performance. It was shown that adding a graphene layer to the SPR sensor structure can improve the tuning range and sensitivity [19] as a protection layer to the plasmonic metal from oxidation and this can lead to more stability of the performance.…”
Section: Introductionmentioning
confidence: 99%